2021
DOI: 10.5194/jbji-6-321-2021
|View full text |Cite
|
Sign up to set email alerts
|

<i>Candida</i> fracture-related infection: a systematic review

Abstract: Abstract. Background: The aim of this study is to summarize and improve knowledge regarding a Candida fracture-related infection (CFRI) through a systematic review on the topic, accompanied by a case report. Methods: A systematic review and meta-analysis based on PRISMA statement were conducted on the CFRI topic. The following combined search terms were used to explore PubMed, Cochrane, and the Embase database: “fungal infection”, “candida”, “fracture related infection”, “bone infection”, “orthopedic infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…At the same time, we noted that the total number of infections showed a downward trend with the passage of time, which may be related to our trauma treatment policy and the improvement in medical standards. No fungus-induced FRI was observed in our study, which occurs most often in immunosuppressed populations and in those receiving long-term non-standard broad-spectrum antibiotic therapy ( De Meo et al, 2021 ).…”
Section: Discussionmentioning
confidence: 53%
“…At the same time, we noted that the total number of infections showed a downward trend with the passage of time, which may be related to our trauma treatment policy and the improvement in medical standards. No fungus-induced FRI was observed in our study, which occurs most often in immunosuppressed populations and in those receiving long-term non-standard broad-spectrum antibiotic therapy ( De Meo et al, 2021 ).…”
Section: Discussionmentioning
confidence: 53%
“…Although rare, there have been reports of fungal fracture related infections. A systematic review in 2021 64 reported 5 cases of candida grown on samples from FRI. Risk factors for fungal infection included open wounds, prolonged antibiotic therapy and immunodeficiency. The reoperation rate was 33% and prolonged antifungal therapy was required (mean time 8.8 weeks).…”
Section: "Beyond Bacteria"mentioning
confidence: 99%
“…While most infections are caused by bacteria, fungal infections are accountable for 1% of all prosthetic joint infections, and they often require multiple surgeries with a temporary removal of the prosthesis to cure 2 of 24 the infection, if possible at all [6,7,10]. Nevertheless, re-infections are common, and they lead to even higher mortality rates [6,7] Fungal infections of fractures are less prevalent than fungal infections in total joint arthroplasty [11]. The most frequent cause of fracture infections is the direct inoculation of open fractures or traumatic injuries contaminated with soil [12][13][14].…”
Section: Introductionmentioning
confidence: 99%